Impact of COVID-19 Crisis on Exam Anxiety Levels among Bachelor Level University Students - Alsaady, Isra; Gattan, Hattan; Zawawi, Ayat; Alghanmi, Maimonah; Zakai, Haytham (Mediterranean Journal of Social Sciences, 2020)
COVID-19 crisis had a huge impact on education and academics. Besides, it might have generated public fear and worry. All these factors might affect students’ performance and wellbeing and might increase stress levels especially during exams. Therefore, this study will investigate the impact of COVID-19 crisis on student’s exam anxiety and its relationship with other factors. A cross-sectional study was conducted by distributing exam anxiety survey electronically to Saudi universities bachelor students, two hundred and seventy-two students have responded to the survey. The results have shown that both female and male student have high anxiety levels. And no significant correlation was found between any demographic data and anxiety level, except the gender, as female students have a higher anxiety level than male students. In conclusion, COVID-19 might had generated a high exam anxiety level, especially in female students. Therefore, facilitating initiatives might be considered to improve students’ performance during this crisis.